2013
DOI: 10.2306/scienceasia1513-1874.2013.39.511
|View full text |Cite
|
Sign up to set email alerts
|

Biomass derived tar decomposition over coal char bed

Abstract: The effect of coal char on the decomposition of rice straw derived tar was investigated in a two-stage fixed bed reactor. The reactor was divided into a pyrolysis zone (upper part) and a volatile-char contacting zone (lower part). Rice straw was pyrolysed at different temperatures in the upper part. Coal char, prepared by the pyrolysis of Indonesian coal at either 600°C (char600) or 800°C (char800), was located in the lower part. Volatiles from the rice straw (upper part) were produced and then came in contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
4
18
0
Order By: Relevance
“…This is in agreement with the findings of Hosokai et al [37], who stated that molecules with more fused rings were decomposed faster, and with the preferential adsorption for PAH observed on AC by Mastral et al [17]. Selectivity towards multi-ring aromatics has also been observed by researchers working with thermal decomposition of pyrolysis-derived tars [64,65].…”
Section: Chemical Adsorption and Catalysissupporting
confidence: 91%
“…This is in agreement with the findings of Hosokai et al [37], who stated that molecules with more fused rings were decomposed faster, and with the preferential adsorption for PAH observed on AC by Mastral et al [17]. Selectivity towards multi-ring aromatics has also been observed by researchers working with thermal decomposition of pyrolysis-derived tars [64,65].…”
Section: Chemical Adsorption and Catalysissupporting
confidence: 91%
“…Thus, it is necessary to develop a tar reforming system with high thermal efficiency and without catalyst poisoning or deactivation. The effective decomposition of tar compounds over biomass/coal-derived chars has been frequently reported (Abu El-Rub, 2008;Gilbert et al, 2009;Krerkkaiwan et al, 2015;Krerkkaiwan et al, 2013;Sun et al, 2011). Naphthalene, representative of the most refractory compounds among tar constituents, was decomposed almost completely over chars or charcoals from different biomass/coals within a short gas residence time (less than 0.25 s) in a fixed-bed reactor (Abu El-Rub et al, 2004b;Fuentes-Cano et al, 2013).…”
Section: In Situ Tar Reforming Processmentioning
confidence: 93%
“…Carbon‐based catalysts, such as pyrolysis char, activated carbon, and gasified char, are attractive catalysts for the tar removal process, due to their effectiveness and relatively low cost. Many researchers have identified the catalytic performance of carbon‐based catalysts, such as coal char and wood char, as well as the co‐pyrolysis char, in terms of the increased gas production and tar conversion. El‐Rub et al reported that biochar made from pine wood pyrolysis was the most effective catalyst for naphthalene conversion at 900°C, among the other low cost catalysts (dolomite, olivine, and spent fluid catalytic cracking catalyst [FCC]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the lifetime of the biochar was longer. Coal char and co‐pyrolysis char were also used for tar steam reforming to decrease tar yield and increase gas products, especially H 2 and CO production . There are two main aspects related to the catalytic performance of the carbon‐based catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation